PERKEMBANGAN SPASIAL PENGGUNAAN LAHAN REAL ESTAT DAN PENGARUHNYA TERHADAP PEREKONOMIAN KOTA SURAKARTA - Muhammad Arif; - Soeratno (Universitas Muhammadiyah Semarang, 2015)
Real estate is one of the region physical growth indicators, an increasing in this sector showing the human and their activity in that area, real estate also serves as the locomotive of the economy, increased the growth of the real estate will trigger a multiplier in other sectors, especially the service, trade and industry sector. This paper designed to determine the development of real estate based on the distribution, movement patterns and its impact on the economy of Surakarta city. This study used two approaches, the first approach is spatial analysis for determine distribution, movement patterns of real estate and the second is statistical approaches for determine correlationbetween real estate and economic growth in Surakarta City. This study show that residential real estate directly growth to the Jebres sub-district, Banjarsari, and Serengan. Service sector and trade leads and clustered at sub-district Serengan and Laweyan, while the industrial sector isconcentrated in the region and parts of Serengan and Pasar Kliwon. Pattern of real estate developments in Surakarta identic with multiple nuclei concept and the central activity (CBD) located in the Pasar Kliwon sub district and Ir Sutami road (Jebres sub-district). Statistical approach result that there is no significant correlation between the growth of real estate and economic growth in Surakarta between the years 1993 - 2011 at 5 or 10 percent degree of error. Highest use analysis shows that the service sector is located in Pasar Kliwon and Banjarsari district, while trade and industry sectors present in the Pasar Kliwon and Serengan.Keyword: real estate, spatial development, economic growth, correlation.